Competitividad en micro y pequeñas empresas en el sector lácteo del cantón Latacunga - Maenza Torres, Anahi Fernanda (2022)
When talking about competitiveness in a globalized world, reference is made to the factor that drives all types of companies to be profitable in the market, either creating a plus through continuous improvement and innovation, or being at the forefront to maintain a solid position. In the present research work, the competitiveness index of the dairy industry of micro and small enterprises, located in Latacunga on the Cotopaxi province, was determined. The competitiveness index based on the BID map consists of two components, first business and second cantonal; the same ones that measure two dimensions of competitiveness, one given by the business conditions in which companies operate; and, other which measures the conditions of the region where the companies are located. In this post-pandemic study, the effect that COVID 19 had on organizations is considered, due to the economic recession, the dairy industry was affected both in production as well as mainly in its merchandising, systems, hindering the provision of resources for its effective operation, thus affecting its competitiveness. This study has a quantitative approach and a descriptive scope, since surveys were applied to an important sample of companies in the sector, in order to determine the indices mentioned above. With respect to the business competitiveness index, it was estimated by adapting the BID Competitiveness Map and as a result of this procedure. The cantonal competitiveness index was obtained with a value of 0.66 and the business index of 0.41. Based on these results, the sectoral competitiveness index was prepared, whose result was 0.54, which showed a decrease in the competitiveness of companies of 5.31% compared to 2019.